A Preliminary Evaluation of CBT-Based Group Counseling for Sexual Awareness Among Female Adolescents - Ika Ariyati; Nurul Aisyah; Aprezo Pardodi Maba; Hanimatul Fauziyah; Marensa Trihamidah (Kuras Institute, 2026)
Sexual awareness is an important component of adolescent health education, particularly in institutional environments where discussions related to sexuality may be culturally sensitive. Islamic boarding schools represent a context in which preventive and culturally appropriate educational approaches are needed to support adolescents’ understanding of personal boundaries and sexual safety. This study examined the preliminary effectiveness of Cognitive Behavioral Therapy (CBT)–based group counseling in improving sexual awareness among female adolescents in an Islamic boarding school setting. A quasi-experimental pretest–posttest control group design was used. Twenty-two female students aged 12–15 years were allocated into an intervention group and a control group. The intervention group participated in six structured CBT-based group counseling sessions focusing on cognitive restructuring, self-awareness, assertiveness, and behavioral reflection, while the control group received no intervention. Sexual awareness was measured using the Sexual Awareness Questionnaire before and after the intervention. Data were analyzed using an independent samples t-test. Results indicated a statistically significant difference between groups, with the intervention group demonstrating higher posttest sexual awareness scores compared with the control group, t(20) = 3.158, p = .005. These findings suggest that CBT-based group counseling may support improvements in sexual awareness among female adolescents in religious educational settings. Further research with larger samples and longer follow-up periods is recommended to strengthen evidence for effectiveness.